The value of the knolwedge of vetrinary science to the farmer - Pearson, Charles Randolph (My University, 1894)
Introduction: In the various branches which are related to agriculture there is perhaps no study needed more and studied less than that of Vetrinary Science. I do not mean that every farmer should be a Vetrinary Surgeon, for under that branch we find as many complicated problems as in any science. But I mean that every farmer should have a good clear understanding of the more common principles which are called for in every day life in the care of his stock. From a moral standpoint the care we give our stock should be next to the care of ourselves, but too often they are the last thing we think of. There is also a financial side to the care of stock and of this alone I wish to speak. When we see a man unhitch his horses from a harvester and take them to a water trough for a cold drink of water we are sure that he is a person who often has sick horses and not only sick ones but dead ones. Cold water on a sweaty horses stomach means deranged digestion and in a large percent of the cases spasmodic colic is the immediate result. This disease is caused by any foreign substance in the stomach. It is a spasmodic contraction of the muscular walls of the intestines. It is a painful disease and very dangerous because it is liable to turn into inflammation of the bowels and if it does the percent of loss is very great even under expert treatment.
Citation: Pearson, Charles Randolph. The value of the knolwedge of vetrinary science to the farmer. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Veterinary science; Horse; Spasmodic colic; Equine; Theses; Manuscripts (documents)